ChemInform Abstract: Bifunctional Primary Amine‐Squaramide Catalyzed Enantioselective Intramolecular Michael Addition of Keto‐enones: A Convenient Process to the Stereocontrolled Construction of trans‐Dihydrobenzofuran Skeletons. Issue 1 (7th January 2014) - Liu, Yunting; Lu, Aidang; Hu, Keling; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract The scalable, highly diastereo‐ and enantioselective title reaction proceeds smoothly to yield the trans‐dibenzofuran derivatives (II) and (IV).